The Maintenance of Gorontalo Language through Teaching The Local Content at Elementary Schools - Moon H. Otoluwa; Zulkifli Tanipu; Novi Rusnarty Usu; Rasuna Talib (IJLECR (International Journal of Language Education and Cultural Review), 2016)
The current condition exposes the degradation of number of speakers even the use of Gorontalo language. It is proved by the data which show that almost 40% of respondents cannot speak Gorontalo language actively. As a consequence, the maintenance of Gorontalo language is a must to prevent this phenomenon to be worse. One of the effective ways to maintain Gorontalo language is teaching the Gorontalo language through the local content at elementary schools. Moreover, the teaching process should involve cultural and linguistic aspects of the language.